(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Rape remains one of the world’s most underreported crimes for various reasons such as shame, fear of retribution from the abuser, lack of remedies for the victim’s condition, fear of skepticism, and social stigmatization. Rape has received significant attention as the number of victims is rising exponentially & rape is expected to be a critical social issue. The definition of rape vary as time and place, however rape is recognized as a crime that typically is committed by a male forcing another person to have sexual intercourse against their will, intercourse by force. The study is confined to Varanasi district of U.P. State. The current study is by nature exploratory. It has different levels of methodological strategies which helped me arrive nearer to the reality of rape as a phenomenon. In the present study we have gathered the facts both from the primary and the secondary sources.